Monitoring molecular dynamics of bacterial cellulose composites reinforced with graphene oxide by carboxymethyl cellulose addition - Sanchís, M.J.; Carsí, M.; Gómez, C.M.; Culebras, M.; Gonzales, K.N.; Torres, F.G. (Elsevier, 2017)
Broadband Dielectric Relaxation Spectroscopy was performed to study the molecular dynamics of dried Bacterial Cellulose/Carboxymethyl Cellulose-Graphene Oxide (BC/CMC-GO) composites as a function of the concentration of CMC in the culture media. At low temperature the dielectric spectra are dominated by a dipolar process labelled as a β-relaxation, whereas electrode polarization and the contribution of dc-conductivity dominate the spectra at high temperatures and low frequency. The CMC concentration affects the morphological structure of cellulose and subsequently alters its physical properties. X-ray diffractometry measurements show that increasing the concentration of CMC promotes a decrease of the Iα/Iβ ratio. This structural change in BC, that involves a variation in inter- and intramolecular interactions (hydrogen-bonding interactions), affects steeply their molecular dynamics. So, an increase of CMC concentration produces a significantly decrease of the β-relaxation strength and an increase of the dc-conductivity.
Keywords: Dielectric relaxation; Cellulose--Mechanical properties; https://purl.org/pe-repo/ocde/ford#2.10.00